Analysis of the FADN system implementation in the Republic of Serbia - Ivkov, Ivana <1980> (Alma Mater Studiorum - Università di Bologna, 2016)
One among many other preconditions in the field of agriculture for Serbia’s accession to the EU is establishment of the Farm Accountancy Data Network (FADN) system. It can improve both on-farm and agricultural policy decision making processes by providing valuable information on physical, structural, economic and financial data. Republic of Serbia does not have farm accounting legal base and therefore the agricultural hold-ers are not obliged to keep records in order to have accurate income calculations. In line with this, Serbian FADN system has been established. As a consequence to aforementioned, this deliverable is an earliest attempt to examine the use-fulness and suitableness of the FADN system implementation in the Republic of Serbia. The applied EU FADN methodology is described, clarifying the basic definitions (universe of agri-cultural holdings, field of observation, sample selection, standard output, etc.). Harmonization and application of this methodology in the Republic of Serbia is described as well. In this research it was observed Serbian FADN life cycle from 2012 to 2015, with the main focus on 2013. Comparative research method was used in a particular areas of this study, which aimed to make comparisons across different FADN organizational infrastructures of certain EU Member States and Republic of Serbia, as well as to make comparisons of the first Serbian FADN results with the same results of a few selected EU Member States. In the pre-conclusion section the emphases is given on SWOT analyses, which gives an assessment of the FADN system implementation in the EU and in the Republic of Serbia. In addition to this, recommendations are given in order to achieve better FADN system implementation in the Repub-lic of Serbia. Research findings indicated that the Serbian FADN system is still under development, faces many challenges, and needs to be further improved and strengthened.